2013
DOI: 10.1371/journal.pone.0076329
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Like Dog Placenta Cells Afford Neuroprotection against Ischemic Stroke Model via Heat Shock Protein Upregulation

Abstract: In this study, we investigated the dog placenta as a viable source of stem cells for stroke therapy. Immunocytochemical evaluation of phenotypic markers of dog placenta cells (DPCs) cultured in proliferation and differentiation medium revealed that DPCs expressed both stem cell and neural cell markers, respectively. Co-culture with DPCs afforded neuroprotection of rat primary neural cells in a dose-dependent manner against oxygen-glucose deprivation. Subsequent in vivo experiments showed that transplantation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…On the day of transplantation, β‐gal‐positive hBMEPCs were dissociated into single cells by brief trypsin treatment and suspended in PBS at 4 × 10 6 cells per milliliter and kept on ice until transplantation. The cell suspension was injected slowly for 5 minutes into the jugular vein of four randomly selected rats at 48 hours after tMCAO as we previously described .…”
Section: Methodsmentioning
confidence: 99%
“…On the day of transplantation, β‐gal‐positive hBMEPCs were dissociated into single cells by brief trypsin treatment and suspended in PBS at 4 × 10 6 cells per milliliter and kept on ice until transplantation. The cell suspension was injected slowly for 5 minutes into the jugular vein of four randomly selected rats at 48 hours after tMCAO as we previously described .…”
Section: Methodsmentioning
confidence: 99%
“…[ 62 ] Another study of in vivo and in vitro stroke models found that dog placenta cells (DPC) had neuroprotective properties by way of Hsp27. [ 49 ] In this study, DPCs were shown to increase the expression of Hsp27 near the area surrounding the ischemic lesion. [ 45 ] Since Hsp27 has been shown to have neuroprotective effects, its increased expression is indicative of the mechanism through which DPCs confer neuroprotection.…”
Section: Amnion Cell Therapy In Inflammation-plagued Strokementioning
confidence: 74%
“…[ 48 ] Among the various immunomodulating effects of ASCS are the inhibition of metalloproteinases, reduction of antigen-presenting cells, upregulation of heat shock protein 27 (hsp27), suppression of T cell multiplication, and modification of M1 microglia, which favor inflammation, into the anti-inflammatory M2 type. [ 49 50 51 ] This reversal from an environment favorable for inflammation into an anti-inflammatory one promotes the regeneration of damaged brain cells. [ 24 ]…”
Section: Role Of Amniotic Stem Cells In Modulating Inflammationmentioning
confidence: 99%
“…Using dog placenta as a source of embryonic-like stem cells, Yu et al [ 60 ] demonstrated increased cell survival of primary rat neurons/astrocytes that were cocultured with these cells after OGD treatment. The authors demonstrated that the beneficial effect may result from an upregulation of heat shock protein 27.…”
Section: Brain Ischemiamentioning
confidence: 99%